Influence of Support Acidity and Ir Content on the Selective Ring Opening of Decalin over Ir/SiO 2 –Al 2 O 3 - D'ippolito, Silvana Andrea (2017)
The influence of the addition of HCl and Ir (1 wt %) to different SiO2−Al2O3 supports of varying silica content was studied in the reaction of selective ring opening of decalin. The addition of HCl to silica−alumina supports containing 70 and 80 wt % SiO2 was found to have little influence in the distribution of reaction products compared to the calcined supports. The incorporation of Ir to the silica−alumina catalysts has a beneficial effect, increasing the decalin conversion, being this effect more noticeable in the low acidity supports, i.e., those containing 30−40 wt % SiO2. The iridium-containing materials display the highest yield of cracking products, ring opening products, and ring contraction products. Increasing the reaction temperature promotes cracking and dehydrogenation but markedly decreases the selectivity to ring contraction products. At 350 °C a slight decrease in selectivity to ring opening products occurs, though the overall increase in conversion results in an increased yield of these products. An optimum ratio between the acid sites and metal activity that favors the formation of ring opening products was found. At lower acid sites/metal activity ratios the isomerization reaction which leads to C5 cycle isomers is low, and ring opening by hydrogenolysis is limited as a consequence. On the other hand, at high acid sites/metal activity ratios the cracking reactions are favored, decreasing the yield of RO products.